Identification of prosomatostatin in pancreatic islets. - Patzelt, C (1980)
A 12.5-kilodalton protein not related to insulin or glucagon was detected in pulse-chase-labeled rat islets of Langerhans. Although this protein reacted poorly with various somatostatin antisera, analysis of two-dimensional peptide maps showed that it contains all of the tryptic fragments of somatostatin, which is located at its COOH terminus. Proteolytic conversion of the putative prosomatostatin, which took place parallel to the processing of proinsulin and proglucagon in pulse-chase experiments, coincided with the appearance of newly synthesized somatostatin and proceeded without the apparent involvement of major intermediate forms.